2016
DOI: 10.1002/ptr.5658
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Adhesion, Biofilm Formation and Quorum Sensing ofCampylobacter jejunibyEuodia ruticarpa

Abstract: Thermophilic campylobacters are a major cause of bacterial food-borne diarrhoeal disease. Adherence and biofilm formation are key elements of Campylobacter jejuni persistence in unfavourable environmental conditions. The phytochemical analysis of Euodia ruticarpa fruit ethanol solution extract (EREE) indicated that the major compounds were evodiamine (1), rutaecarpine (2) and evocarpine (9). E. ruticarpa fruit ethanol solution extract, compounds 1 and 2 as well as a mixture of quinolinone alkaloids with 41.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 34 publications
(52 reference statements)
3
43
0
1
Order By: Relevance
“…Since Campylobacter adhesion to epithelial cells is an important step for colonization (Jin et al, 2001; Hermans et al, 2011a), a reduction in this virulence attribute could potentially reduce colonization in birds. Bezek et al (2016) had similar findings with extracts from Euodia ruticarpa . In addition, these researchers observed that other virulence attributes, including biofilm formation and quorum sensing were also affected by the phytochemical.…”
Section: Discussionsupporting
confidence: 69%
“…Since Campylobacter adhesion to epithelial cells is an important step for colonization (Jin et al, 2001; Hermans et al, 2011a), a reduction in this virulence attribute could potentially reduce colonization in birds. Bezek et al (2016) had similar findings with extracts from Euodia ruticarpa . In addition, these researchers observed that other virulence attributes, including biofilm formation and quorum sensing were also affected by the phytochemical.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, these citrus extracts reduced C. jejuni invasion of and adhesion to HeLa cells and the expression of the virulence genes cadF and ciaB [26]. On the other hand, Bezek et al [27] showed good C. jejuni QS reduction with Euodia ruticarpa but no connection to C. jejuni biofilm formation. This indicates high sensitivity of the C. jejuni LuxS system, and thus QS signaling, to outside stressors, such as treatments with natural extracts.…”
Section: Discussionmentioning
confidence: 95%
“…The AI-2 bioassays were performed as previously described [27,28] with some modifications. These QS inhibition bioassays were carried out using the biosensor reporter strain V. harveyi BB170 [27], which was grown for 16 h at 30 • C and 150 rpm mixing to approximately 10 7 CFU/mL and used at the final concentration of 5 × 10 3 CFU/mL in AB medium. The C. jejuni CFSs were added to the suspensions of the reporter strain to a final concentration of 10% (v/v) (i.e., 20 µL CFS added to 180 µL reporter strain suspension).…”
Section: Autoinducer-2 Bioassaymentioning
confidence: 99%
“…The surfaces of equipment used for food handling, storage, and processing represent major sources of Campylobacter contamination (Nguyen et al, ; Simões et al, ). As is known, C. jejuni forms monospecies biofilms on stainless steel, glass (e.g., fibre, beads, coverslips), nitrocellulose membranes, and various plastic surfaces (Bezek et al, ; Teh et al, ). Campylobacter attached to food contact surfaces can form biofilms and survive not just the food processing conditions (as has been seen for the dairy industry and during meat processing) but also the addition of antimicrobials and other disinfection treatments (Joshua et al, ).…”
Section: Discussionmentioning
confidence: 99%